Analisis Profitabilitas Dan Leverage Terhadap Harga Saham Perusahaan Sektor Food & Beverage Yang Terdaftar Di BEI Periode Tahun 2020-2023 - Gisela Putri Particia Ramadhan; Henny Dwijayani; Betty Rahayu (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2025)
This study discusses the profitability and leverage ratios using the Return On Assets (ROA) and Return On Equity (ROE) indicators for measuring profitability and Debt To Equity Ratio (DER) for measuring leverage on the stock price of Food & Beverage (F&B) compainies listed on the Indonesia Stock Exchange (2020-2023), the stock price used the closing price. The population used F&B compainies listed on the IDX 2020-2023. The sampling technique used was purposive sampling. The samples used were 8 F&B compainies listed on the DX. The data analysis technique useds multiple linear analysis with the SPSS 21 tool. The results obtained from the t test (partial) show that Return On Assets (ROA) has a significant effect on Stock Price, Return On Equity (ROE) has a siginificant effect on Stock Price, Debt To Equity Ratio (DER) has no siginificant effect on Stock Price. Through the F test (simultaneous) the results show that Return On Assets (ROA), Return On Equity (ROE), and Debt To Equity Ratio (DER) simultaneously have an influence on Stock Prices.